Role of Copeptin in Febrile Seizures (Journal of Pharmaceutical Negative Results, 2023)
Differentiation between febrile seizures and non-ictal events associated with fever such as shivering or dizziness is challenging. Therefore, precise diagnosis of FS after paroxysmal episodes associated with fever is often hindered by the lack of an objective biomarker, some biomarkers for predicting or diagnosing FS have attracted attention.